Astrocytes as an HIV CNS Reservoir: Highlights and reflections of an NIMH-sponsored symposium - Al-Harti, Lena (J Neurovirol, 2018)
This a summary of a National Institute of Mental Health (NIMH) sponsored symposium that was focused on the role of astrocytes as a reservoir of the human immunodeficiency virus in the brain. The talks were grouped into four themes. The first theme reviewed the evidence for HIV infection of astrocytes and discussed the challenges in the use of traditional methods of immunostaining and in situ hybridization for detection of infected astrocytes. The second theme focused on mechanisms of HIV entry into astrocytes and discussed CD4 independent mechanisms such as receptor mediated endocytosis and transmission of HIV by cell-to-cell contact with infected lymphocytes. The third theme focused on epigenetic regulation of HIV latency in astrocytes and other factors such as cytokines and transcriptional factors regulating HIV replication in astrocytes. The fourth theme focused on therapeutic approaches such as gene editing to block persistently infected astrocytes. A discussion that followed was focused on major unanswered questions in the field and future directions for research.